STUDENTS' VOCABULARY LEARNING STRATEGIES(A DESCRIPTIVE STUDY OF VOCABULARY LEARNING STRATEGIES USED BY EIGHTH GRADERS IN ONE OF JUNIOR HIGH SCHOOLS IN INDRAMAYU) - Daniel Bahar, - (2010)
The study investigated the vocabulary learning strategies which were used by the eighth graders in one of junior high school in Indramayu. There were 36 students involved in this study, and categorized into three levels; high achievers (12 students), Average achievers (12 students), low achievers (12 students). This study was mostly conducted in qualitative research design, but certain findings were presented in simple descriptive statistics. In collecting the data, this study used three different instruments: questionnaire, interview and document analysis. Based on findings, the most frequent strategy used by the whole students was "bilingual dictionary". This strategy was also considered as the most helpful according to the students' opinion. Meanwhile, among many considerations practicality became the main reason for the students in nominating certain strategy as the most helpful strategies. Furthermore, for the strategies used by the three categories of students, it was found that the high achievers tended to use "guess from textual context" strategy, the average achievers tended to use "take notes in class" strategy, and the low achievers tended to use "ask classmates for meaning" strategy. Thus, it can be inferred that the eighth graders of junior high school involved in this study were aware of the strategies in learning vocabulary, yet they still needed teacher assistance to improve their vocabulary learning.